2007
DOI: 10.1186/1471-2202-8-9
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-like aggregates of neuronal tau induced by formaldehyde promote apoptosis of neuronal cells

Abstract: Background: The microtubule associated protein tau is the principle component of neurofibrillar tangles, which are a characteristic marker in the pathology of Alzheimer's disease; similar lesions are also observed after chronic alcohol abuse. Formaldehyde is a common environmental contaminant and also a metabolite of methanol. Although many studies have been done on methanol and formaldehyde intoxication, none of these address the contribution of protein misfolding to the pathological mechanism, in particular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 61 publications
0
33
0
Order By: Relevance
“…Our previous results showed that extracellular tau aggregates were toxic to neuronal cells [27]. We detected intracellular tau aggregation by formaldehyde in cell apoptosis.…”
Section: Resultsmentioning
confidence: 63%
See 3 more Smart Citations
“…Our previous results showed that extracellular tau aggregates were toxic to neuronal cells [27]. We detected intracellular tau aggregation by formaldehyde in cell apoptosis.…”
Section: Resultsmentioning
confidence: 63%
“…Tau-40 contains 44 lysine and 2 cysteine residues (NP_005901) [1], [30], which should react with formaldehyde. 5,5′-Dithio-bis(2-nitrobenzoic acid) (DTNB) modification was used to check the thiol groups of tau incubated under different concentrations of formaldehyde (Figure 6) whilst o -phthaldehyde (OPT) modification was used to detect the amino groups of tau under the same conditions as described previously [27]. Both DTNB absorbance (412 nm) and OPT fluorescence (E m 455 nm/E x 340 nm) decreased following the increase of formaldehyde concentration.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This assay (Rojas Quijano et al, 2006) was performed by adding a freshly-prepared stock solution of Congo Red in 100 mmol/L potassium phosphate (pH 7.2) to RCC-fibrinogen adducts (3 mg/mL) to give a final Congo Red concentration of 5 μmol/L as described previously (Nie et al, 2007).…”
Section: Congo Red Binding Assaymentioning
confidence: 99%